(untitled) (Editora Impacto Científico, 2025)
INTRODUCTION: The therapeutic properties and socioeconomic impacts of Andiroba (Carapa guianensis) have aroused the interest of researchers from various health areas (Agência Pará, 2022). This discussion becomes even more relevant when considering that the Amazon will host the United Nations Conference on Climate Change (COP 30), scheduled to take place in 2025, an event of great importance for global environmental agendas. In this context, it is essential to develop studies that investigate, in an integrated manner, both the medicinal aspects of Andiroba and its social and economic effects in the Amazon region, guiding the sustainable exploration of a species with great therapeutic potential. (Vieira; Oliveira; Galvão, 2025).